New argentine seedless varieties INTA - Pugliese, Maria Beatriz; Quiroga Martin, Maria Isabel; Barcia Poblete, Fernando Andres; Pacheco, Daniela; Infante, Silvina; Diaz Sambueza, Alejandra Mariela (South African Society for Enology and Viticulture and The South African Table Grape Industry, 2026)
Presentación en diapositivas